2018
DOI: 10.1021/jacs.8b12140
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Carbon Isotope Exchange of Pharmaceuticals with Labeled CO2

Abstract: A copper-catalyzed procedure enabling dynamic carbon isotope exchange is described. Utilizing the universal precursor [ 14 C]CO 2 , this protocol allows to insert, in one single step, the desired carbon tag into carboxylic acids with no need of structural modifications. Reducing synthetic costs and limiting the generation of radioactive waste, this procedure will facilitate the access to carboxylic acids containing drugs and accelerate early 14 C-based ADME studies supporting drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
100
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 36 publications
(41 reference statements)
3
100
0
3
Order By: Relevance
“…The counter-cation of the carboxylate salt impacts carboxylate exchange reactivity ( Fig 2B). The carboxylic acid of 1 is not reactive, no 13 CO 2 exchange or protodecarboxylation was observed in DMF at + and Na + salts of 1 react more slowly, while transition metal salts (Zn 2+ or Cu 2+ ) are inert. The use of polar aprotic solvents is essential for the transformation, reactions conducted in THF, DCE, or water resulted in recovery of unlabeled 1.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The counter-cation of the carboxylate salt impacts carboxylate exchange reactivity ( Fig 2B). The carboxylic acid of 1 is not reactive, no 13 CO 2 exchange or protodecarboxylation was observed in DMF at + and Na + salts of 1 react more slowly, while transition metal salts (Zn 2+ or Cu 2+ ) are inert. The use of polar aprotic solvents is essential for the transformation, reactions conducted in THF, DCE, or water resulted in recovery of unlabeled 1.…”
mentioning
confidence: 96%
“…An understanding of this phenomenon can be exploited to prepare isotopically labelled drug molecules and synthetic precursors in an operationally trivial manner. exchange when placed under an atmosphere of 13 CO 2 . In a reaction where approximately seven equivalents of 13 CO 2 is supplied (13 mL of CO 2 at ~1 atm, dissolved 13 CO 2 concentration of 0.25 M), equilibrium between 12 C and 13 C is achieved in 15 hours (Fig 2A, red trace).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cantat, Audisio, [9] and co-workers also used [ 14 C]CO 2 gas as the isotope source for aC IE reaction on aromatic and heteroaromatic carboxylic acids (Figure 1c). They reported that aromatic carboxylates undergo thermal CO 2 extrusion in the presence of ac opper salt, which is followed by the reaction of the organometallic intermediates with labelled gas to yield the corresponding 14 C-labelled acids.T his CIE procedure was carried out on cesium salts of the carboxylic acids with 3equiv [ 14 C]CO 2 in only 2hours but at ah igh reaction temperature (150 8 8C).…”
mentioning
confidence: 99%
“…Cantat, Audisio [9] und Mitarbeiter nutzten ebenfalls [ 14 C]CO 2 -Gas als Isotopenquelle füre ine CIE-Reaktion mit aromatischen und heteroaromatischen Carbonsäuren (Abbildung 1c). Sie berichteten, dass aromatische Carboxylate in Gegenwart eines Kupfersalzes eine thermische CO 2 -Extrusion eingehen, woraufhin die organometallischen Zwischenprodukte mit markiertem Gas zu den entsprechenden 14 Cmarkierten Säuren umgesetzt werden.…”
unclassified